A numerical study of planar detonations - Tamagno, José (2012)
A numerical study on the buildup and propagation of planar detonation waves in H2 + Air combustible mixtures, based on theuse of unsteady Euler equations coupled with source terms to account for rates controlled chemical activity, is presented. The computer solver works with 13 chemical species and 33 different one step reactions of a H2 O2 N2 combustion mechanism. The detonation process is initiated via the energy provided by an igniter which acts as a driver of a shock tube driving through a combustible mixture a blast (or strong shock), accompanied by exothermic chemical changes. It is shown that for each equivalence ratio of the combustible mixture, the detonation can only be triggered if the igniter energy deposition equals or exceeds a computed minimum value. When the igniter energy deposition is less than this minimum, the combustion zone start to decouple from the blast front and if that energy is diminished even more, the combustion could nottake place. A particular way of generating sustained overdriven detonations, is also considered.